Framework for Effective Cross-border Knowledge Transfer - Ling, Chong Mahn; Yen, Yuen Yee; Yen, Wendy Teoh Ming (International Review of Management and Marketing, 2016)
Effective cross-border knowledge transfer can help to improve the competitiveness of the multinational companies, improve production process or product development, lower the operation cost, reduce errors, and improve profitability. However, cross-border knowledge transfer has always been a challenge for most of the companies especially when it involves communication and trust among a group of local and employees from different cultural background. Cultural diversity always causes the failure of knowledge transfer in actual implementation. Therefore, this study intends to propose a framework for managing cultural diversity and trust of cross-border knowledge transfer in Iskandar Development Region. The objective of this study is to propose a comprehensive framework to examine the key factors that affect employee’s participation in cross-border knowledge transfer. Based on focus group study with management of selected multinational companies in Iskandar Development Region, a comprehensive research framework is developed with ten independent variables (individualism/ collectivism, power distance, uncertainty avoidance, affective/ neutral, achievement/ ascription, and monochronic/ polychromic, trust, attitude, social support, and facilitating conditions), and a dependent variable (participation in cross-border knowledge transfer). Apart from contributing to the literature of knowledge management, the findings of the study also serve as a strong foundation for academics and future researchers to conduct future study in related industry and region. Keywords: Cross-border, knowledge transfer, framework, key factors. JEL Classifications: O1; O2; O4